The educational dynamics of media - Culkin, John.; American Library Association. Conference (91st). (Los Angeles, Calif. CREDR Corp., 1973)
A three-part presentation on media use, media programs and the relationships among media, arts, sciences, and libraries.
Tape 1 (1 hr.) An overview of media use / John Culkin -- The reasons for media: what makes programs goodn / Janice Gallinger -- Tape 2 (1 hr.) The natural fit: art, music, medicine / Luraine Tansey, David Hall, Alfred Strohlein -- Tape 3 (50 min.). Designing libraries for media use / David Crossman -- Relating libraries to media facilities : fusion or symbiosisn / Donald L. Ely.
American Library Association, 91st annual conference. Media: man, material, machine.
Moderator, Ellsworth Mason.
Keywords: Media programs (Education) -- Congresses; Audio-visual library service -- Congresses; Mass communication; Education; Communication; Library science